Utility of video-assisted method for identifying and preserving the external branch of the superior laryngeal nerve during thyroidectomy - Ding, Zhaoming; Sheng, Ruinan; Zhang, Liang; Han, Jihua; Chen, Mengshi; Bi, Wen; Zhao, Xuesong; Zhang, Jiewu; Nie, Chunlei (Frontiers in Surgery, 2023)
Background: The EBSLN is vulnerable to damage during thyroidectomy, results in voice related complications, negatively affect patient quality of life, routine identification of the EBSLN prior to surgical manipulation is necessary for a complication-free thyroidectomy. We aimed to validate a video-assisted procedure for identifying and preserving the external branch of the superior laryngeal nerve (EBSLN) during thyroidectomy and analyze the EBSLN Cernea classification and the localization of the nerve entry point (NEP) from the insertion of the sternothyroid muscle. Methods: A prospective descriptive study was performed; 134 patients, who scheduled for lobectomy with an intraglandular tumor max diameter ≤ 4 cm and without extrathyroidal extension, were randomly divided into the video-assisted surgery (VAS) and conventional open surgery (COS) groups. We used the video-assisted surgical procedure for visually identifying the EBSLN directly, and compared the differences in the visual identification rate and total identification rate of the two groups. We also measured the localization of the NEP using the insertion of the sternothyroid muscle as a reference. Results: There was no statistically significant difference in clinical characteristics between the two groups. The visual identification rate and total identification rate were significantly higher in the VAS group than the COS group (91.04% vs. 77.61%, 100% vs. 89.6%). The EBSLN injury rate was 0 in both groups. The mean vertical distance (VD) of the NEP from the sternal thyroid insertion was 1.18 mm (SD 1.12 mm, range, 0–5 mm), with approximately 88.97% of the results occurring within the 0–2 mm range. The mean horizontal distance (HD) was 9.33 mm (SD 5.03 mm, range, 0–30 mm), with over 92.13% of the results occurring within the 5–15 mm range. Conclusion: Both the visual and total identification rates of the EBSLN were significantly higher in the VAS group. This method provided a good visual exposure rate of the EBSLN, aiding in identifying and protecting the EBSLN during thyroidectomy.